FORMATION OF FOREIGN-LANGUAGE COMMUNICATIVE COMPETENCES IN LANGUAGE LEARNERS USING ENGLISH PROVERBS AND SAYINGS (Scientific journal of the Fergana State University, 2024)
This article aims to examine the hypothesis that students who are exposed to English proverbs and sayings will develop a better understanding of the source and target languages and cultures, leading to improved translation accuracy and fluency. Also, it proves the results of the research that was conducted among Fergana State university students to support the proposed hypothesis.